Porous silicon carbon negative electrode material of lithium ion battery as well as preparation method and application of porous silicon carbon negative electrode material

By combining activated silicon nanoparticles with graphite and asphalt, and using environmentally friendly chloride salt as template agent, an efficient and environmentally friendly porous silicon carbon negative electrode material was prepared, which solved the problems of poor conductivity and volume expansion in lithium-ion batteries, and achieved Efficient cycle stability and simplified process flow.

CN119230809APending Publication Date: 2024-12-31GUANGDONG NANHUA ENERGY CONSERVATION & LOW CARBON DEVELOPMENT RESEARCH INSTITUTE +1

Patent Information

Application Number
CN202411126895.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-16
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing lithium-ion battery anode materials have problems such as poor conductivity, serious volume expansion, complex preparation process, high cost and heavy pollution, which limits the industrial application of silicon-carbon composite materials.

Method used

The surfactant is used to activate the silicon nanoparticles and mix them uniformly with graphite, and then ball milling and annealing with asphalt and potassium chloride. The porous silicon-carbon composite material is prepared by using environmentally friendly and non-toxic salts as template agents to avoid toxic corrosion. The use of reagents simplifies process steps and reduces costs.

Benefits of technology

It has achieved high first-time Coulomb efficiency, excellent cycle stability and environmentally friendly and recyclable porous silicon carbon anode material, solved the problems of poor conductivity and volume expansion, simplified the preparation process and reduced costs, and is suitable for large-scale industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230809A_ABST
    Figure CN119230809A_ABST
Patent Text Reader

Abstract

The invention discloses a porous silicon-carbon negative electrode material of a lithium ion battery as well as a preparation method and application of the porous silicon-carbon negative electrode material. The preparation method comprises the following steps: firstly, activating silicon nanoparticles by using a surfactant, so that the silicon nanoparticles are positively charged, and agglomeration of the silicon nanoparticles is avoided; secondly, nano active silicon and graphite are uniformly mixed and ball-milled, so that the active silicon is anchored in a graphite layer, and the conductivity of the whole material is improved; and uniformly mixing and ball-milling the silicon / graphite composite material, asphalt and potassium chloride, and then annealing and washing to obtain the porous silicon-carbon composite material. The activated nano silicon can effectively prevent agglomeration of nano silicon particles, the porous carbon prepared by taking potassium chloride as a template agent has the characteristics of environmental protection and no pollution, the potassium chloride can be recycled, and the prepared porous silicon carbon negative electrode material can enable a lithium ion battery to have relatively high initial coulombic efficiency and excellent cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion battery negative electrode, and specifically relates to a lithium ion battery porous silicon-carbon negative electrode with high initial coulombic efficiency, excellent cycle stability and environmentally friendly and recyclable template agent, and a preparation method and application in lithium ion batteries, especially to a porous silicon-carbon negative electrode material. Background Art

[0002] As a traditional negative electrode material for lithium-ion batteries, graphite has a low theoretical specific capacity of only 372 mAh g -1 , which can no longer meet the demand for high energy density batteries. Therefore, it is urgent to develop a lithium-ion battery negative electrode material with high energy density, good safety, and environmental protection.

[0003] In recent years, silicon-based negative electrode materials have gradually come into people's view and have been widely studied. Silicon-based materials have high theoretical capacity (4200mAh g -1 ), low working potential (0.2-0.4V), good safety performance and abundant reserves, making it one of the most promising next-generation lithium-ion negative electrode materials. However, silicon-based materials also face huge challenges, such as low electronic conductivity (10 -5 -10 -3 S cm -1 ), severe volume expansion (>300%), etc. Severe volume expansion can cause the electrode material to detach from the current collector, resulting in failure of the active material. These problems will greatly affect the first coulombic efficiency, rate performance and cycle stability, and to some extent limit the practical application of silicon-based materials.

[0004] At present, the main methods used to solve the problems of low conductivity and volume expansion are silicon-based material nano-sizing and silicon-carbon composites. Silicon materials are constructed into nanoscale structures such as nanosheets, nanoparticles and porous structures, or silicon is coated on the surface of conductive carbon materials. Silicon nanostructured materials are obtained by reducing the particle size, which can effectively shorten the transmission path of electrons and ions, reduce the internal stress and strain caused by lithium ion diffusion, thereby reducing the internal stress during volume change, avoiding structural rupture or crushing, reducing irreversible capacity loss, and thus improving cycle stability. Carbon-based materials do not change much in volume during lithium insertion / delithiation, have good cycle stability, and excellent conductivity. Carbon and silicon are both group IV elements with similar chemical properties and good bonding. Moreover, carbon materials have low manufacturing costs and simple processes. Therefore, carbon materials are the first choice to ensure that silicon electrode materials do not fail. Silicon-carbon composite materials with different structural designs can effectively alleviate the problems of poor conductivity and volume expansion of silicon materials. The preparation of porous silicon-carbon composite materials is one of the most effective methods.

[0005] Usually, porous silicon-carbon negative electrode materials are prepared by using an intermediate template, etching silicon and silicon dioxide with hydrofluoric acid (HF) to obtain a porous structure. HF is a highly toxic drug and has strong corrosiveness. The presence of HF greatly increases the difficulty of operation and the cost of preparation. For example, micron-scale porous silicon-carbon composites (M-pSi@C) are prepared by a spray drying process and a magnesium thermal reduction method and used as lithium-ion battery negative electrodes. However, the preparation process is complicated, including multiple steps such as spray drying and magnesium thermal reduction, and porous carbon is obtained by etching with HF, which is highly dangerous and difficult to achieve industrial application. It is reported that the gap between the silicon layer and the carbon layer can be constructed by the volatilization of low-melting-point elemental sulfur, but the introduction of elemental sulfur will cause environmental pollution. Therefore, these methods have a series of problems such as environmental pollution, complex preparation process, and high cost, which greatly limits the large-scale industrial application of silicon-carbon composite materials.

[0006] In summary, how to design and prepare a porous silicon-carbon composite material with simple process, green safety, low cost and excellent electrochemical performance to address the problems of complex preparation process, high cost, heavy pollution and certain safety hazards of porous silicon-carbon negative electrodes is of great significance to the development of lithium-ion battery negative electrode materials. Summary of the invention

[0007] In order to solve the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing a porous silicon-carbon negative electrode material for lithium-ion batteries with high initial coulombic efficiency, excellent cycle stability and environmentally friendly and recyclable template agent.

[0008] The present invention firstly activates silicon nanoparticles by using a surfactant, so that the silicon nanoparticles are positively charged and the agglomeration of the silicon nanoparticles is avoided. Secondly, nano-active silicon and graphite are uniformly mixed and ball-milled, so that the active silicon is anchored in the graphite layer, thereby improving the conductivity of the overall material. Then, the silicon / graphite composite material is uniformly mixed and ball-milled with asphalt and potassium chloride, and then annealed and washed to obtain a porous silicon-carbon composite material. Asphalt has a large number of components such as aromatic ethers and aromatic hydrocarbons, which can well coat silicon / graphite during the exothermic process of ball milling, greatly reducing the volume expansion of silicon, and asphalt is widely available, low in price, and high in carbon yield. Environmentally friendly and non-toxic chloride salts are used as pore-forming templates, and the prepared porous silicon-carbon composite material has abundant pores, effectively shortening the transmission path of electrons and ions, and the chloride salts can also be recycled and reused by evaporation and crystallization, saving costs.

[0009] The porous silicon-carbon composite material prepared by the present invention has a simple process and can be applied in large-scale industrial applications. The introduction of graphite improves the conductivity of the overall material. The porous structure is prepared by using chloride salt as a template, avoiding the use of corrosive and toxic reagents such as HF and sublimated sulfur, promoting the diffusion of lithium ions and shortening the transmission path of electrons, and also making the silicon-carbon composite material have a higher first coulomb efficiency and excellent cycle stability. The prepared porous carbon skeleton greatly alleviates the huge volume expansion of silicon particles, thereby greatly enhancing the long-cycle stability of the prepared electrode material.

[0010] Therefore, one of the advantages of the present invention is that a porous silicon-carbon composite material is prepared using chloride salt as a template. The process steps are simple and can be applied industrially on a large scale. Chloride salt is environmentally friendly and pollution-free, can be recycled and reused, and saves costs. The second advantage is that the porous silicon-carbon composite material prepared using chloride salt has a rich pore structure, shortens the diffusion distance of lithium ions and the electron transmission path, and effectively improves the first coulomb efficiency and cycle stability of the silicon-carbon composite material, solving the problems of severe volume expansion and poor conductivity of the silicon negative electrode. The third advantage is that asphalt is used as a carbon source, and nano-silicon / graphite can be uniformly wrapped by ball milling without the action of any solvent, and can be further carbonized to form a porous outer carbon layer under the action of the template. The fourth advantage is that the active silicon that is prone to agglomeration is first anchored in graphite, and then the porous silicon-carbon composite material is prepared by a simple ball milling method with the carbon source and the template, thereby improving the electrochemical performance of the composite material.

[0011] Another object of the present invention is to provide a lithium ion battery porous silicon-carbon negative electrode material prepared by the above preparation method.

[0012] Another object of the present invention is to provide application of the above-mentioned porous silicon-carbon negative electrode material for lithium-ion batteries in lithium-ion batteries.

[0013] The purpose of the present invention is achieved through the following technical solutions:

[0014] A method for preparing a porous silicon-carbon negative electrode material for a lithium-ion battery comprises the following steps:

[0015] (1) adding nano silicon particles and a surfactant into water, ultrasonically treating, and drying to obtain positively charged nano active silicon;

[0016] (2) uniformly mixing nano-active silicon and graphite, and ball milling to obtain a silicon / graphite composite material;

[0017] (3) uniformly mixing the silicon / graphite composite material with asphalt and chloride salt, ball milling, annealing, washing, and drying to obtain a porous silicon-carbon negative electrode material for a lithium-ion battery;

[0018] (4) Evaporating the liquid after washing in step (3) to recover the chloride salt.

[0019] Preferably, the size of the nano silicon particles in step (1) is 10-100 nm.

[0020] Preferably, the surfactant in step (1) is at least one of hexadecyltrimethylammonium bromide and octadecyltrimethylammonium chloride.

[0021] Preferably, the mass ratio of the nano-silicon particles to the surfactant in step (1) is 1:(2-3); more preferably 1:2.5.

[0022] Preferably, the ratio of the surfactant to water in step (1) is 1 g: (20-200) ml.

[0023] Preferably, the ultrasonic treatment time in step (1) is 10-60 minutes.

[0024] Preferably, the mass ratio of the nano-active silicon to graphite in step (2) is 1:(0.2-20); more preferably 1:0.5.

[0025] Preferably, the ball milling time in step (2) is 3-8 hours.

[0026] Preferably, the rotation speed of the ball mill in step (2) is 400-700 rpm, more preferably 550 rpm.

[0027] Preferably, the mass ratio of the silicon / graphite composite material to asphalt in step (3) is 3:(1-4); more preferably 3:2.

[0028] Preferably, the mass ratio of the asphalt to the chloride salt in step (3) is 1:(0.5-4); more preferably 1:(1-3); most preferably 1:2.

[0029] Preferably, the chloride salt in step (3) is at least one of potassium chloride, sodium chloride and lithium chloride.

[0030] Preferably, the ball milling time in step (3) is 3-10 h.

[0031] Preferably, the rotation speed of the ball mill in step (3) is 400-700 rpm, more preferably 550 rpm.

[0032] Preferably, the annealing treatment in step (3) is carried out at a temperature of 550-850°C for 2-5 hours; more preferably, the annealing treatment is carried out at a temperature of 550-750°C for 3-4 hours; or the annealing treatment is carried out at a temperature of 650-850°C for 2-3 hours.

[0033] Preferably, the annealing treatment in step (3) is performed under an inert gas atmosphere; more preferably, the inert gas is at least one of nitrogen and argon.

[0034] Preferably, the heating rate of the annealing treatment in step (3) is 2-10°C / min.

[0035] Preferably, the drying temperature in step (3) is 40-100° C. and the drying time is 5-15 h.

[0036] Preferably, the temperature of the evaporation treatment in step (3) is 80-120°C.

[0037] A porous silicon-carbon negative electrode material for lithium-ion batteries prepared by the above preparation method.

[0038] Application of the above-mentioned porous silicon-carbon negative electrode material for lithium-ion batteries in lithium-ion batteries.

[0039] This patent will be described in more detail below.

[0040] Step (1) uses a surfactant to modify silicon nanoparticles to obtain positively charged silicon nanoparticles, thereby avoiding silicon agglomeration and improving the dispersibility of silicon in the silicon-carbon composite material, so that the obtained silicon-carbon composite material is more uniform.

[0041] In step (2), the ball milling time of silicon and graphite is 3-8 hours. If the ball milling time is too short, silicon is unevenly distributed in the graphite, which cannot well improve the conductivity and stability of the overall material; if the ball milling time is too long, the nano-active silicon is oxidized by air during the ball milling process, resulting in a decrease in active silicon and a decrease in specific capacity.

[0042] In step (3), the mass ratio of asphalt to chloride salt is 1:(0.5-4), the annealing temperature is 550-850℃, and the time is 2-5h. If the amount of chloride salt used is too little, fewer pores are formed, and the effect of reducing the volume expansion of silicon is not obvious; if the amount of chloride salt used is too much, more pores are formed, the structure is prone to collapse, and the cyclic stability of the silicon-carbon composite material is reduced. If the annealing temperature is too low and the time is too short, the asphalt is not completely carbonized, and the conductivity and stability of the silicon-carbon composite material are poor; if the annealing temperature is high and the time is too long, the degree of graphitization of the asphalt-derived carbon is too high, the mechanical stress decreases, and it is difficult to buffer the huge volume expansion of silicon. The stability of the silicon-carbon composite material is reduced, and the energy consumption is high, resulting in a significant increase in production costs.

[0043] In step (3), deionized water is used to remove chloride salts, thereby obtaining a porous structure. The abundant pores are beneficial for shortening the diffusion distance of lithium ions and the electron transmission path, and also effectively improve the initial coulombic efficiency and cycle stability of the silicon-carbon composite material.

[0044] Step (4) evaporates the chloride salt solution at a certain temperature and recycles it for reuse, thus saving costs and causing no environmental pollution.

[0045] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0046] (1) The present invention anchors active silicon in the graphite layer, and further utilizes low-value-added asphalt as a carbon source, and mixes it with potassium chloride for ball milling for carbon coating, thereby avoiding the problem of poor rate performance caused by poor conductivity of silicon and effectively alleviating the volume expansion of silicon.

[0047] (2) The present invention uses chloride salt as a template, thereby avoiding the use of toxic and corrosive reagents HF and sublimed sulfur, being environmentally friendly and pollution-free, and the chloride salt can be recycled and reused, thus saving costs.

[0048] (3) The preparation process of the present invention is simple, does not require the use of organic solvents, is environmentally friendly and non-toxic, and does not require complex steps such as chemical vapor deposition and magnesium thermal reduction, and can be applied on a large scale in industry. The rich pore structure shortens the diffusion distance of lithium ions and the electron transmission path, and also effectively improves the first coulomb efficiency and cycle stability of the silicon-carbon composite material, providing an effective way to solve the problems of silicon volume expansion and poor conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 This is a flow chart for preparing a porous silicon-carbon negative electrode for a lithium-ion battery according to Example 1 of the present invention.

[0050] Figure 2 This is the XRD diagram of the porous silicon-carbon negative electrode of the lithium ion battery prepared in Example 1 of the present invention.

[0051] Figure 3 This is the Raman graph of the porous silicon-carbon negative electrode of the lithium ion battery prepared in Example 1 of the present invention.

[0052] Figure 4 This is a scanning electron microscope image of the porous silicon-carbon negative electrode of a lithium-ion battery prepared in Example 1 of the present invention.

[0053] Figure 5 This is a scanning electron microscope image of the lithium ion battery silicon-carbon negative electrode prepared in Comparative Example 1 of the present invention.

[0054] Figure 6 This is a rate performance diagram of the porous silicon-carbon negative electrode for lithium-ion batteries prepared in Example 1 of the present invention.

[0055] Figure 7 This is a cycle performance diagram of the porous silicon-carbon negative electrode of a lithium-ion battery prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0056] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.

[0057] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.

[0058] Example 1

[0059] Weigh 2.5 g of hexadecyltrimethylammonium bromide (CTAB) and dissolve it in 250 mL of deionized water. Add 1.0 g of nano-silicon powder (30 nm) to the above solution, stir, ultrasonicate for 30 min, vacuum filter, and dry at 60°C for 12 h to obtain active nano-Si with positive charge.

[0060] 1.0 g of active nano-Si was mixed with 0.5 g of graphite (G) and ball-milled at 550 rpm for 5 h to obtain Si@G composite material. 1.5 g of Si@G composite material, 1.0 g of asphalt and 2.0 g of KCl were weighed and mixed evenly, and ball-milled at 550 rpm for 5 h. Subsequently, the ball-milled product was annealed at 650 °C in N2 atmosphere for 3 h, with a heating rate of 5 °C min -1 , cooled to room temperature, washed several times with deionized water and anhydrous ethanol, and dried at 60°C for 12 h to obtain a porous silicon-carbon composite material.

[0061] Example 2

[0062] Weigh 2.5 g of hexadecyltrimethylammonium bromide (CTAB) and dissolve it in 250 mL of deionized water. Add 1.0 g of nano-silicon powder (30 nm) to the above solution, stir, ultrasonicate for 30 min, vacuum filter, and dry at 60°C for 12 h to obtain active nano-Si with positive charge.

[0063] 1.0 g of active nano-Si was mixed with 0.5 g of graphite (G) and ball-milled at 550 rpm for 5 h to obtain Si@G composite material. 1.5 g of Si@G composite material, 1.0 g of asphalt and 2.0 g of KCl were weighed and mixed evenly, and ball-milled at 550 rpm for 5 h. Subsequently, the ball-milled product was annealed at 850 °C in N2 atmosphere for 3 h, with a heating rate of 5 °C min -1 , cooled to room temperature, washed several times with deionized water and anhydrous ethanol, and dried at 60°C for 12 h to obtain a porous silicon-carbon composite material.

[0064] Example 3

[0065] Weigh 2.5 g of hexadecyltrimethylammonium bromide (CTAB) and dissolve it in 250 mL of deionized water. Add 1.0 g of nano-silicon powder (30 nm) to the above solution, stir, ultrasonicate for 30 min, vacuum filter, and dry at 60°C for 12 h to obtain active nano-Si with positive charge.

[0066] 1.0 g of active nano-Si was mixed with 0.5 g of graphite (G) and ball-milled at 550 rpm for 5 h to obtain Si@G composite material. 1.5 g of Si@G composite material, 1.0 g of asphalt and 2.0 g of KCl were weighed and mixed evenly, and ball-milled at 550 rpm for 5 h. Subsequently, the ball-milled product was annealed at 650 °C in N2 atmosphere for 4 h, with a heating rate of 5 °C min -1 , cooled to room temperature, washed several times with deionized water and anhydrous ethanol, and dried at 60°C for 12 h to obtain a porous silicon-carbon composite material.

[0067] Example 4

[0068] Weigh 2.5 g of hexadecyltrimethylammonium bromide (CTAB) and dissolve it in 250 mL of deionized water. Add 1.0 g of nano-silicon powder (30 nm) to the above solution, stir, ultrasonicate for 30 min, vacuum filter, and dry at 60°C for 12 h to obtain active nano-Si with positive charge.

[0069] 1.0 g of active nano-Si was mixed with 0.5 g of graphite (G) and ball-milled at 550 rpm for 5 h to obtain Si@G composite material. 1.5 g of Si@G composite material, 1.0 g of asphalt and 1.0 g of KCl were weighed and mixed evenly, and ball-milled at 550 rpm for 5 h. Subsequently, the ball-milled product was annealed at 650 °C in a N2 atmosphere for 3 h, with a heating rate of 5 °C min -1 , cooled to room temperature, washed several times with deionized water and anhydrous ethanol, and dried at 60°C for 12 h to obtain a porous silicon-carbon composite material.

[0070] Comparative Example 1 (without adding template potassium chloride)

[0071] Weigh 2.5 g of hexadecyltrimethylammonium bromide (CTAB) and dissolve it in 250 mL of deionized water. Add 1.0 g of nano-silicon powder (30 nm) to the above solution, stir, ultrasonicate for 30 min, vacuum filter, and dry at 60°C for 12 h to obtain active nano-Si with positive charge.

[0072] 1.0 g of active nano-Si was mixed with 0.5 g of graphite (G) and ball-milled at 550 rpm for 5 h to obtain Si@G composite material. 1.5 g of Si@G composite material and 1.0 g of asphalt were weighed and mixed evenly, and ball-milled at 550 rpm for 5 h. Subsequently, the ball-milled product was annealed at 650 °C in N2 atmosphere for 3 h, with a heating rate of 5 °C min -1 , cooled to room temperature, washed several times with deionized water and anhydrous ethanol, and dried at 60 °C for 12 h to obtain a non-porous silicon-carbon composite material.

[0073] Comparative Example 2 (Nano-silicon not activated)

[0074] 1.0 g of nano-Si (30 nm) was mixed with 0.5 g of graphite (G) and ball-milled at 550 rpm for 5 h to obtain Si@G composite material. 1.5 g of Si@G composite material, 1.0 g of asphalt and 2.0 g of KCl were weighed and mixed evenly, and ball-milled at 550 rpm for 5 h. Subsequently, the ball-milled product was annealed at 650 °C in N2 atmosphere for 3 h, with a heating rate of 5 °C min -1 , cooled to room temperature, washed several times with deionized water and anhydrous ethanol, and dried at 60°C for 12 h to obtain a porous silicon-carbon composite material.

[0075] Comparative Example 3 (without adding graphite to anchor active nano-silicon)

[0076] Weigh 2.5 g of hexadecyltrimethylammonium bromide (CTAB) and dissolve it in 250 mL of deionized water. Add 1.0 g of nano-silicon powder (30 nm) to the above solution, stir, ultrasonicate for 30 min, vacuum filter, and dry at 60°C for 12 h to obtain active nano-Si with positive charge.

[0077] 1.0 g of active nano-Si, 1.0 g of asphalt and 2.0 g of KCl were mixed and ball-milled at 550 rpm for 5 h. Subsequently, the ball-milled product was annealed at 650 °C in a N2 atmosphere for 3 h at a heating rate of 5 °C min -1 , cooled to room temperature, washed several times with deionized water and anhydrous ethanol, and dried at 60°C for 12 h to obtain a porous silicon-carbon composite material free of graphite.

[0078] Comparative Example 4 (Potassium sulfate as template)

[0079] Weigh 2.5 g of hexadecyltrimethylammonium bromide (CTAB) and dissolve it in 250 mL of deionized water. Add 1.0 g of nano-silicon powder (30 nm) to the above solution, stir, ultrasonicate for 30 min, vacuum filter, and dry at 60°C for 12 h to obtain active nano-Si with positive charge.

[0080] 1.0g active nano-Si was mixed with 0.5g graphite G and ball-milled at 550rpm for 5h to obtain Si@G composite material. 1.5g Si@G composite material, 1.0g asphalt and 2.0g K2SO4 were weighed and mixed evenly, and ball-milled at 550rpm for 5h. Subsequently, the ball-milled product was annealed at 650℃ in N2 atmosphere for 3h, with a heating rate of 5℃min -1 , cooled to room temperature, washed several times with deionized water and anhydrous ethanol, and dried at 60°C for 12 h to obtain a porous silicon-carbon composite material.

[0081] Comparative Example 5 (Using Lignin as Carbon Precursor)

[0082] Weigh 2.5 g of hexadecyltrimethylammonium bromide (CTAB) and dissolve it in 250 mL of deionized water. Add 1.0 g of nano-silicon powder (30 nm) to the above solution, stir, ultrasonicate for 30 min, vacuum filter, and dry at 60°C for 12 h to obtain active nano-Si with positive charge.

[0083] 1.0 g of active nano-Si was mixed with 0.5 g of graphite (G) and ball-milled at 550 rpm for 5 h to obtain Si@G composite material. 1.5 g of Si@G composite material, 1.0 g of pre-hydrolyzed lignin and 2.0 g of KCl were weighed and mixed evenly, and ball-milled at 550 rpm for 5 h. Subsequently, the ball-milled product was annealed at 650 °C in N2 atmosphere for 3 h, with a heating rate of 5 °C min -1 , cooled to room temperature, washed several times with deionized water and anhydrous ethanol, and dried at 60°C for 12 h to obtain a porous silicon-carbon composite material.

[0084] Comparative Example 6 (One-step mixing ball milling method)

[0085] Weigh 2.5 g of hexadecyltrimethylammonium bromide (CTAB) and dissolve it in 250 mL of deionized water. Add 1.0 g of nano-silicon powder (30 nm) to the above solution, stir, ultrasonicate for 30 min, vacuum filter, and dry at 60°C for 12 h to obtain active nano-Si with positive charge.

[0086] 1.0 g of active nano-Si, 0.5 g of graphite (G), 1.0 g of asphalt and 2.0 g of KCl were mixed and ball-milled at 550 rpm for 5 h. Subsequently, the ball-milled product was annealed at 650 °C in a N2 atmosphere for 3 h at a heating rate of 5 °C min -1 , cooled to room temperature, washed several times with deionized water and anhydrous ethanol, and dried at 60°C for 12 h to obtain a porous silicon-carbon composite material.

[0087] Assemble button-type half-cells, the negative electrode material is the electrode material obtained in the examples and comparative examples, the counter electrode is a lithium sheet, the electrolyte is 1 mol / L LiPF6 as the solute, and the volume ratio of 1:1 ethylene carbonate (EC) and diethyl carbonate (DEC) are used as solvents. The entire battery installation process is completed in an argon-protected glove box. The battery constant current charge / discharge performance test is performed in the voltage range of 0.01V to 2.5V using the Neware battery performance test system, and the rate performance test is performed at 0.1A g -1 , 0.2A g -1 , 0.5Ag -1 , 1.0A g -1 , 2.0A g -1 and 5.0A g -1 completed at current density.

[0088] The different lithium ion battery negative electrodes prepared in the above examples and comparative examples were applied to lithium ion batteries and subjected to electrochemical tests and material characterization. The results are shown in Table 1 and Figure 1-7 .

[0089] Table 1 Performance of silicon-carbon negative electrodes prepared in all examples and comparative examples for lithium-ion batteries

[0090]

[0091]

[0092] Table 1 shows that the porous silicon-carbon negative electrode for lithium-ion batteries prepared in Example 1 is 0.1Ag -1 The initial capacity is 1562.7 mAh g -1 , the Coulombic efficiency is 85.8% at 1A g -1 The capacity retention rate after 100 cycles at a current density of is 75.5%. It can be seen that the porous silicon-carbon negative electrode for lithium-ion batteries prepared by the present invention has a high first coulombic efficiency and excellent cycle stability, which is significantly better than similar materials, and the cycle stability of all embodiment samples is better than other comparative samples. This is mainly due to the active silicon anchored in the graphite layer, which solves the problem of silicon conductivity and alleviates the volume expansion of silicon to a certain extent. Asphalt has a large number of components such as aromatic ethers and aromatic hydrocarbons. The heat generated during the ball milling process enables the asphalt to coat the silicon / graphite well, greatly inhibiting the volume expansion of silicon and effectively avoiding the collapse of the electrode material structure. In addition, if Figure 4 As shown, using potassium chloride as a pore-forming template, the rich pore structure in the porous silicon-carbon composite material obtained shortens the diffusion distance of lithium ions and the electron transmission path, and can also relieve the stress caused by the volume expansion of silicon, thereby effectively improving the first coulombic efficiency and cycle stability of the silicon-carbon composite material, providing an effective way to solve the volume expansion and poor conductivity of silicon.

[0093] In Table 1, Comparative Example 1 does not use a template to form pores, and a silicon-carbon composite material without a pore structure is obtained, which cannot effectively shorten the diffusion distance of lithium ions and the electron transmission path, and is also difficult to buffer the stress generated by silicon volume expansion. The effect of inhibiting silicon volume expansion is also relatively weakened, resulting in a decrease in the first coulomb efficiency and cycle stability. Its first coulomb efficiency is 77.5%, and at 1A g -1After 100 cycles at the same current density, the capacity retention rate was 70.9%. In Comparative Example 2, the silicon nanoparticles were not activated, and the silicon nanoparticles were easily agglomerated during ball milling and annealing heat treatment. The silicon distribution in the prepared silicon-carbon composite material was uneven, and the local volume expansion was too large, resulting in the local preferential collapse of the electrode material, which in turn led to the deterioration of the overall mechanical properties of the electrode material and the decrease in cycle stability. In Comparative Example 3, no graphite was added to anchor the active nano-silicon particles. The overall conductivity of the material was poor, resulting in a low first coulomb efficiency of only 75.8%. Moreover, the asphalt carbon layer alone could not effectively inhibit the volume expansion of silicon, resulting in a relatively low stability of the electrode material at 1A g -1 After 100 cycles at the same current density, the capacity retention rate was only 66.1%. Comparative Example 4 used potassium sulfate as the pore-forming template, and the first cycle capacity, first coulomb efficiency and capacity retention rate of the prepared electrode material were all lower than those of Example 1. Comparative Example 5 used lignin as the carbon precursor, and at 1A g -1 After 100 cycles at the same current density, the capacity retention rate was 66.5%, indicating that lignin could not wrap silicon / graphite well, the huge volume expansion of silicon caused the lignin-derived carbon layer to break, and even the active material fell off from the current collector, causing the battery to fail.

[0094] Figure 1 This is a flow chart of the porous silicon-carbon negative electrode material for lithium-ion batteries prepared in Example 1 of the present invention. As can be seen from the flow chart, the operation steps are simple, no solvent is required, the process is green, and it is suitable for large-scale industrial application.

[0095] Figure 2 This is the XRD diagram of the porous silicon-carbon negative electrode of the lithium ion battery prepared in Example 1 of the present invention. The prepared silicon-carbon composite material contains only silicon, graphite and amorphous carbon without other impurities.

[0096] Figure 3 This is the Raman graph of the silicon-carbon negative electrode material prepared in Example 1 of the present invention, proving the presence of silicon and carbon and the absence of other impurities.

[0097] Figure 4 This is a scanning electron microscope image of the porous silicon-carbon negative electrode of a lithium-ion battery prepared in Example 1 of the present invention. As can be seen from the figure, the material presents a block structure, which is different from Figure 5 , Figure 4 It has a distinct pore structure, and the abundant pores promote the diffusion of lithium ions, electron transport and alleviate the huge volume change of silicon.

[0098] Figure 5 This is a scanning electron microscope image of a silicon-carbon composite material without a pore structure obtained in Comparative Example 1 of the present invention. As can be seen from the image, the material presents a block structure without obvious pores.

[0099] Figure 6This is a rate performance diagram of the porous silicon-carbon negative electrode for lithium-ion batteries prepared in Example 1 of the present invention. Under different current densities, the specific capacity of the porous silicon-carbon negative electrode for lithium-ion batteries can reach a stable state after several cycles, and the ... -1 Transition to 5.0A g -1 It can still quickly stabilize when the current density returns to 0.2A g -1 , the specific capacity recovered to a higher level, indicating that the material has excellent rate performance and stable structure.

[0100] Figure 7 This is a cycle performance diagram of the porous silicon-carbon negative electrode of a lithium-ion battery prepared in Example 1 of the present invention. It can be seen that the electrode has a stable structure, excellent cycle stability, and the volume expansion of silicon is significantly suppressed.

[0101] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a porous silicon-carbon negative electrode material for a lithium-ion battery, characterized in that: The following steps are involved: (1) adding nano silicon particles and a surfactant into water, ultrasonically treating, and drying to obtain positively charged nano active silicon; (2) uniformly mixing nano-active silicon and graphite, and ball milling to obtain a silicon / graphite composite material; (3) uniformly mixing the silicon / graphite composite material with asphalt and chloride salt, ball milling, annealing, washing, and drying to obtain a porous silicon-carbon negative electrode material for a lithium-ion battery; (4) Evaporating the liquid after washing in step (3) to recover the chloride salt.

2. The method for preparing a porous silicon-carbon negative electrode material for a lithium-ion battery according to claim 1, characterized in that: The mass ratio of the nano-active silicon to graphite in step (2) is 1:(0.2-20); The mass ratio of the silicon / graphite composite material to the asphalt in step (3) is 3:(1-4); The mass ratio of asphalt to chloride salt in step (3) is 1:(0.5-4).

3. The method for preparing a porous silicon-carbon negative electrode material for a lithium-ion battery according to claim 1, characterized in that: The mass ratio of the nano silicon particles to the surfactant in step (1) is 1:(2-3); The surfactant in step (1) is at least one of hexadecyltrimethylammonium bromide and octadecyltrimethylammonium chloride; The size of the nano silicon particles in step (1) is 10-100 nm.

4. The method for preparing a porous silicon-carbon negative electrode material for a lithium-ion battery according to claim 1, characterized in that: The ball milling time in step (2) is 3-8 hours; the ball milling speed is 400-700 rpm; The ball milling time in step (3) is 3-10 hours; the ball milling speed is 400-700 rpm.

5. The method for preparing a porous silicon-carbon negative electrode material for a lithium-ion battery according to claim 1, characterized in that: The chloride salt in step (3) is at least one of potassium chloride, sodium chloride and lithium chloride.

6. The method for preparing a porous silicon-carbon negative electrode material for a lithium-ion battery according to claim 1, characterized in that: The annealing treatment in step (3) is performed at a temperature of 550-850° C. for 2-5 hours. The annealing process is performed in an inert gas atmosphere.

7. The method for preparing a porous silicon-carbon negative electrode material for a lithium-ion battery according to claim 1, characterized in that: The ratio of the surfactant to water in step (1) is 1 g: (20-200) ml; The ultrasonic treatment time is 10-60 minutes; The heating rate of the annealing treatment in step (3) is 2-10°C / min.

8. The method for preparing a porous silicon-carbon negative electrode material for a lithium-ion battery according to claim 1, characterized in that: The mass ratio of asphalt to chloride salt in step (3) is 1:(1-3); The annealing treatment in step (3) is performed at a temperature of 550-750°C for 3-4 hours; or the annealing treatment is performed at a temperature of 650-850°C for 2-3 hours.

9. A porous silicon-carbon negative electrode material for lithium-ion batteries prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the porous silicon-carbon negative electrode material for lithium-ion batteries according to claim 9 in lithium-ion batteries.

Citation Information

Patent Citations

  • Preparation method of rich-hole silicon-carbon negative electrode material of lithium ion battery

    CN114122371A

  • Asphalt-based lithium ion battery silicon-carbon negative electrode material as well as preparation method and application thereof

    CN117038874A

Cited By

  • Carbon-coated silicon-oxygen negative electrode material and preparation method thereof

    CN119864400A

  • Carbon-coated silicon-oxygen negative electrode material and preparation method thereof

    CN119864400B